Motivation and Self-Efficacy in Adolescent Students: A Systematic Review - Otondo-Briceño, Maite; Medina-Hicks, Nicol Alejandra (Revista Electrónica Educare, 2023)
Objective. This research aims to investigate whether academic motivation is linked to academic self-efficacy for promotion in adolescent students in secondary and higher education. The significance of exploring the link between these factors and the degree of influence between them arises from their importance in the academic success of students and the existing gaps in the educational context regarding the intervention of these variables as a whole. Method. A systematic literature review was conducted, analyzing articles indexed in databases such as Web of Science (WOS) and Scopus, published between 2010 and 2020. A protocol was employed to organize the information extracted from articles, focusing on five relevant aspects: source, country, sample, type of study and objective of the study. Results. The results of this research confirm a significant relationship between both variables in adolescent students. Conclusion. Despite the existence of this significant relationship, academic motivation is not considered to be a major factor influencing academic self-efficacy. On the contrary, it is the latter that plays a fundamental role in the development of student motivation. Disseminating the knowledge provided by this study within the scientific and educational community is deemed essential to deepen the research in this domain.